2020
DOI: 10.1101/2020.11.13.20231365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is the relationship between validated frailty scores and mortality for adults with COVID-19 in acute hospital care? A systematic review

Abstract: Background & aimThe COVID-19 pandemic has had a disproportionate impact upon older people; the frailty construct has been used to assess risk of poor outcomes in many settings. The aim of this systematic review was to quantify the association between frailty and COVID-19 in relation to mortality in hospitalised patients.MethodsMedline, Embase and the grey literature were searched for papers from inception to 10th September 2020. Screening (and grading) was undertaken by two reviewers according to pre-defin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…First, this was a retrospective observational study and outcomes were retrospectively adjudicated at each center without central adjudication. Second, some data regarding important cardiovascular risk factors such as dyslipidemia and CAD family history, along with important metrics of overall frailty status were not collected in the dataset and were thus not considered in the multivariate adjustment, which may have affected the study results [ 18 , 19 ]. Similarly, myocardial injury as defined by peak troponin value, was excluded from the multivariate adjustment because this data was only available for a minority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, this was a retrospective observational study and outcomes were retrospectively adjudicated at each center without central adjudication. Second, some data regarding important cardiovascular risk factors such as dyslipidemia and CAD family history, along with important metrics of overall frailty status were not collected in the dataset and were thus not considered in the multivariate adjustment, which may have affected the study results [ 18 , 19 ]. Similarly, myocardial injury as defined by peak troponin value, was excluded from the multivariate adjustment because this data was only available for a minority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the infected patients, up to 20% develop severe disease which requires hospitalisation [ 2 , 3 ]. The association between frailty and consequently Clinical Frailty Scale (CFS) with COVID-19 mortality has been shown in multiple prospective and retrospective studies, a finding which has promoted the incorporation of CFS in the management of COVID-19 patients as suggested by the National Institute for Heath and Care Excellence (NICE) guidelines, despite caution as advised by certain studies against CFS overestimation in COVID-19 prognosis [4] , [5] , [6] , [7] . Frailty prevalence is varied and affects approximately 40% of middle-aged to older patients with age commonly, but not always, correlating with higher scores in the CFS [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Frailty prevalence is varied and affects approximately 40% of middle-aged to older patients with age commonly, but not always, correlating with higher scores in the CFS [8] . To date, a limited number of systematic reviews and even fewer meta-analyses have confirmed the association between CFS and patient mortality with inherent limitations originating from the incorporated studies [ 7 , 9 ]. Nonetheless, until present and to the best of our knowledge, no study has attempted to correlate increasing level of CFS scores, in the context of modifiable and non-modifiable patient factors, with mortality outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, and never without nuance, the more frail an older person is, the worse their health outcomes with COVID-19, compared with those who are fitter, or less frail. 1 , 2 In a multicentre, European, COVID-19 study published in The Lancet Healthy Longevity , Roos Sablerolles and colleagues 3 report that a higher score on the Clinical Frailty Scale (CFS) was associated with greater risk of hospital mortality.…”
mentioning
confidence: 99%
“…The evidence generally supports evaluating frailty as part of managing frail individuals who are acutely ill, especially if age is the alternative measure. 1 , 2 The use of a frailty evaluation is also supported specifically in COVID-19-related presentations. Frailty identification is a starting point to understanding patients who are at risk for death, disability, and loss of independence.…”
mentioning
confidence: 99%